Automatic and creative skills in reading - Leonor Scliar Cabral (Ilha do Desterro)
In this article I will discuss the automatic and creative skills in reading, focusing on the differences between 1) processes involved while learning how to read and processes employed by the proficient reader and 2) knowledge for using language and metalinguistic awareness. The arguments will derive mainly from the definition of reading as a process where the receivers combine the information extracted from the written material with their specialized knowledge activated during this process (i.e. linguistic systems and correspondent rules and enciclopedic knowledge) in order to comprehend, interpret and internalize structured new information and/or to experience aesthetic pleasure. Evidence to illustrate the arguments comes from experiments (1) with pre-school children and beginning readers on narrativity and on the dichotic paradigm, and with illiterate and literate adults with diferent levels of proficiency of reading in a task of erasing an initial syllable and an initial consonant.